Хаджи-Мурат: повести / Л. Н. Толстой ; художник А. Ляшенко - Толстой Лев Николаевич (Советская Россия, 1989)
Экземпляры: с/ф № 10 (20240520) / Инвентарный номер: 52291 / Цена: / Авт.знак: Т 53 / ГРНТИ: 17.82.93 / ББК: 84(2=411.2)-44